1999
DOI: 10.1046/j.1365-2796.1999.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of neurofibromatosis type 1 with an aldosterone‐producing adenoma of the adrenal

Abstract: . Biagi P Alessandri M, Campanella G, Castro R, Totteri A, Fanciullacci M (Abbadia San Salvatore Hospital, Abbadia San Salvatore; Misericordia Hospital, Grosseto; University of Florence, Florence, Italy). A case of neurofibromatosis type 1 with an aldosterone‐producing adenoma of the adrenal (Case Report). J Intern Med 1999; 246: 509–512. Neurofibromatosis type 1 is a phacomatosis. Neurofibromas are the most common tumours associated with the disease, and along with other tumours, make neurofibromatosis type 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Moreover, the data presented in this manuscript support the importance of neurofibromin as a causative factor in adrenal nodular hyperplasia in patients with NF1. Biallelic inactivation of NF1 had been previously reported in one case of adrenal cortical tumor [23], and adrenal adenoma have been described in association with NF1 in several reports [2123]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the data presented in this manuscript support the importance of neurofibromin as a causative factor in adrenal nodular hyperplasia in patients with NF1. Biallelic inactivation of NF1 had been previously reported in one case of adrenal cortical tumor [23], and adrenal adenoma have been described in association with NF1 in several reports [2123]. …”
Section: Discussionmentioning
confidence: 99%
“…Inactivating mutations in NF1 are frequent in adrenal medullary tumors (pheochromocytomas) and it has been shown that NF1 is required for control of proliferation and differentiation in chromaffin cells [20]. While medullary tumors are frequent in NF1, only several cases of adrenal cortex adenoma associated with NF1 have been described in the literature [2123]. However, these cases of sporadic cortical hyperplasia suggest that NF1 might have yet unidentified roles in control of adrenocortical homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Mid-aortic syndrome [13], aldosterone producing tumor [14], aortic coarctations [15] and stretching of the renal artery by neural tumor have also been described as possible determinants. The vascular lesions of renal artery stenosis were characterized by fibromuscular dysplasia [10,16], intramural renal artery Schwann cell proliferation [17], or vascular lesions characterized by an intimal proliferation of spindle cells with destruction of the internal elastic membrane, frequently accompanied by loss or attenuation of the media and fibrosis of the 195 Fig.…”
Section: Discussionmentioning
confidence: 99%